Impact of doping on the density of states and the mobility in organic semiconductors - Zuo, Guangzheng; Abdalla, Hassan; Kemerink, Martijn (Physical review, 2016)
We experimentally investigated conductivity and mobility of poly(3-hexylthiophene) (P3HT) doped with tetrafluorotetracyanoquinodimethane (F4TCNQ) for various relative doping concentrations ranging from ultralow (10−5) to high (10−1) and various active layer thicknesses. Although the measured conductivity monotonously increases with increasing doping concentration, the mobilities decrease, in agreement with previously published work. Additionally, we developed a simple yet quantitative model to rationalize the results on basis of a modification of the density of states (DOS) by the Coulomb potentials of ionized dopants. The DOS was integrated in a three-dimensional (3D) hopping formalism in which parameters such as energetic disorder, intersite distance, energy level difference, and temperature were varied. We compared predictions of our model as well as those of a previously developed model to kinetic Monte Carlo (MC) modeling and found that only the former model accurately reproduces the mobility of MC modeling in a large part of the parameter space. Importantly, both our model and MC simulations are in good agreement with experiments; the crucial ingredient to both is the formation of a deep trap tail in the Gaussian DOS with increasing doping concentration.
Gesehen am 02.12.2019